HUBUNGAN ANTARA PERILAKU MENDENGAR DENGAN KEPUASAN PERKAWINAN SEBUAH KAJIAN PSIKOLINGUISTIK - Yurni Yurni (Jurnal Ilmiah Universitas Batanghari Jambi, 2011)
The purpose of this research was find relationship between listening behavior and sexual satisfaction which hypothesizeda positive relationship between them. The subject of this research were 81 couples from Akuntansi Housing and Nogotirto Elok I housing in Yogyakarta, Indonesia. The data collected by means of two questionnaire that are listening behavior questionnaire and marital satisfaction questionnaire. The data analized by using product moment. The result of this result was there was a positive relationship between listening behavior and marital satisfaction. Emperical means score was bigger than hipotetic score.keyword : behavior, satisfaction, marriage